ASYMMETRIC THREATS IN TERMS OF SAFETY OF RAILWAY SYSTEMS - Andrzej CHUDZIKIEWICZ (Silesian University of Technology, 2021)
This article deals with the problem of new threats that appear in areas that have not been affected by them so far. The considerations concern asymmetric threats and the railway system. The analysis of this issue was carried out on the basis of general information on the problem of asymmetric threats and the knowledge of the railway system, its operation and identified threats that can be attributed to the characteristics of asymmetric threats. The aim of the article is to draw attention to new phenomena that are beginning to affect transport on a global basis, including rail transport.